2015
DOI: 10.1080/02640414.2014.1003582
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic effects of a short-term fatigue protocol on punt-kicking performance

Abstract: The punt kick is a fundamental skill used in several team sports; however, there has been a lack of research on how fatigue affects its technique. The purpose of this study was to determine the effects of short-term fatigue on punt-kicking performance. Eight elite and sub-elite Australian Football players performed maximal drop punt kicks on their preferred leg prior to, during and after a match-specific fatigue protocol. Optotrak Certus collected kinematic data from kick foot toe-off until ball contact. Repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…This increased physiological output during game-play may be explained by superior experience and physical fitness, with Lyons et al (13) demonstrating that physiologically superior elite soccer players were better at preserving technical and perceptual skills throughout the game, relative to their less physically able counterparts. The negative effect of central fatigue on AF maximal kicking distance kinematics (9), as well as kicking accuracy (28) supports the evidence found with soccer players (13). However, the use of field-based and functional kicking (speed and accuracy) tests in AF along with a comparison to kicking efficiency during competition, would have implications for both game and physical demands.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…This increased physiological output during game-play may be explained by superior experience and physical fitness, with Lyons et al (13) demonstrating that physiologically superior elite soccer players were better at preserving technical and perceptual skills throughout the game, relative to their less physically able counterparts. The negative effect of central fatigue on AF maximal kicking distance kinematics (9), as well as kicking accuracy (28) supports the evidence found with soccer players (13). However, the use of field-based and functional kicking (speed and accuracy) tests in AF along with a comparison to kicking efficiency during competition, would have implications for both game and physical demands.…”
Section: Introductionsupporting
confidence: 56%
“…The aim of this study was to determine the effect of maximal aerobic fitness on kicking performance in elite junior AF, with results linked to actual game-play. Previous laboratorybased investigations have reported that cumulative loading of maximal aerobic capacity modifies the kicking kinematics, kicking accuracy, and number of disposals for AF players (9,15,28). Thus, based on this previous work, it was hypothesised that maximal aerobic capacity would impact both kicking performance and competition kicking efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include one or more automated algorithms, spectral analyses, visual inspection of time series data, the effect on parameter values using different cut-offs and previous literature (Coventry, Ball, Parrington, Aughey, & McKenna, 2015;Parrington, Ball, & MacMahon, 2014;Peacock, Ball, & Taylor, 2017). Based on these decisions, as well as considerations around the sample rate for Clearsky, 8 Hz smoothing was chosen for the original smoothing procedure.…”
Section: The Importance Of Filtering and Smoothingmentioning
confidence: 99%
“…This study did not specifically look at deviation in technique just deterioration. A study analysing punt kicking technique after fatigue also found deviation in technique but not deterioration (Coventry, Ball, Parrington, Aughey & McKenna, 2015). A further explanation is that elite level athletes have a much higher resistance to fatigue effects (Spencer, 2016).…”
Section: Fatiguementioning
confidence: 99%